The criteria for identifying the quality of passengers’ transportation by railway and their ranking using AHP method - Sivilevičius, Henrikas; Maskeliūnaitė, Lijana (Transport, 2010)
Passengers’ transportation by rail involving various interested groups, such as managers, service staff and passengers, is a complicated process. Decision‐making persons, organizing railway trips should take into account the interests, needs and possibilities of these particular groups. The solution to some problems associated with passengers’ transportation by rail depends on the experience and qualification of decision‐makers, people who are responsible for the effectiveness of this work. To increase the quality of railway trips, the interested parties, groups of people mentioned above, should coordinate their actions, cooperate with each other in solving the problems and exchange relevant information. Therefore, the increasing quality of passenger transportation is a complicated issue, requiring good professional skills based on knowledge, practical experience, high intellect and new ideas of all the people involved in this process. The current paper presents a diagram showing passenger’s transportation quality with a number of criterion groups A, B, C, D matching the structure and numbers of the questions included in the questionnaires to survey respondents (passengers) and experts (service and administration staff of the train). What is more, the Analytic Hierarchy Process (AHP) methodology based on the pair wise comparison of criteria is used to determine their weights (significances) considering the data obtained from the respondents and experts of each of three categories. Only these questionnaires which have no contradictory estimates are used. Also, the calculation methods demonstrating the results of the survey are provided in this work. One more point such as the data elicited from the respondents who took part in the survey (i.e. passengers from the train running on the international route Vilnius‐Moscow) and experts (i.e. service staff of the already mentioned train and representatives of the administration staff from the Joint‐Stock Company ‘Lithuanian Railways’ (AB , Lietuvos geležinkeliai")) is analyzed. Finally, the conclusions for improving the quality for passenger transportation by Lithuanian railways are given. First published online: 10 Feb 2011